Anionic N-heterocyclic carbenes by decarboxylation of sydnone-4-carboxylates. Issue 16 (19th April 2018) - Lücke, Ana-Luiza; Wiechmann, Sascha; Freese, Tyll; Nieger, Martin; Földes, Tamás; Pápai, Imre; Gjikaj, Mimoza; Adam, Arnold; Schmidt, Andreas
Abstract: Unstable N-heterocyclic carbenes can be masked and stabilized as pseudo-cross-conjugated hetarenium-carboxylates which decarboxylate on warming. This study deals with the decarboxylation of carboxylates of mesoionic compounds to generate anionic N-heterocyclic carbenes. Lithium sydnone-4-carboxylates were therefore prepared via 4-bromosydnones by halogen-lithium exchange with nBuLi and subsequent treatment with carbon dioxide. Protonation gave the corresponding sydnone-4-carboxylic acids. Thermogravimetric measurements in addition to temperature dependent IR spectroscopy proved the decarboxylation of lithium sydnone-4-carboxylates and formation of the corresponding sydnone anions which can be represented as anionic N-heterocyclic carbenes. In DMSO-d6 solution, water favors the decarboxylation. Calculations have been performed to elucidate the mechanism of the decarboxylation in the absence and presence of water. Graphical abstract: Image 1